Self‐Serving Attribution Bias, Overconfidence, and the Issuance of Management Forecasts - LIBBY, ROBERT; RENNEKAMP, KRISTINA (Journal of Accounting Research, 2012)
ABSTRACT Prior studies document that managers consider a variety of costs and benefits when deciding whether to issue earnings forecasts. Using an abstract experiment and a survey of experienced financial managers, we provide evidence that managerial overconfidence may also contribute to this decision. Our experiment shows that participants engage in self‐serving attribution, giving greater weight to internal than external factors as explanations for good performance. This increases confidence in improved future performance, which increases their willingness to issue forecasts. Two facets of the stable individual trait overconfidence, dispositional optimism and miscalibration, also contribute to confidence in improved future performance and willingness to issue forecasts. Consistent with these results, experienced financial manager survey participants believe other managers are likely to overestimate the extent to which they contribute to positive firm performance, and both overoptimism about firm performance and overconfidence in their ability to predict future firm performance contribute to issuance of earnings forecasts.